Clarithromycin Enhances the Antibacterial Activity and Wound Healing Capacity in Type 2 Diabetes Mellitus by Increasing LL-37 Load on Neutrophil Extracellular Traps - Arampatzioglou, Athanasios; Papazoglou, Dimitrios; Konstantinidis, Theocharis; Chrysanthopoulou, Akrivi; Mitsios, Alexandros; Angelidou, Iliana; Maroulakou, Ioanna; Ritis, Konstantinos; Skendros, Panagiotis (Frontiers in Immunology, 2018)
Background: Type 2 diabetes mellitus (T2D) is characterized by susceptibility to bacterial infections and impaired wound healing. Neutrophil extracellular traps (NETs) and the cathelicidin antimicrobial peptide LL-37 have been implicated both in defense against bacterial infections and in wound healing process. Recently, it was shown that macrolide antibiotic clarithromycin induces the release of LL-37-bearing NETs. In T2D there has not been identified any link between NETs and LL-37 and the effect of clarithromycin in neutrophils/NETs is unknown yet. Methods: Peripheral blood neutrophils were obtained from treatment-naive hyperglycemic T2D patients (naive), normoglycemic T2D patients under antidiabetic treatment (well-controlled) and healthy donors (controls). NET release and NET proteins were studied. Co-culture systems of NET structures with E. coli NCTC 9001 and primary skin fibroblasts were deployed to examine the in vitro antibacterial and fibrotic NET properties, respectively. The effect of clarithromycin was also investigated. Analysis was performed using immunofluorescence confocal microscopy, myeloperoxidase-DNA complex and LL-37 ELISA, immunoblotting and qRT-PCR. Results: NETs were characterized by the presence of LL-37, however they lacked antibacterial activity, in both groups of T2D patients. Clarithromycin significantly increased the externalization of LL-37 on NETs generated from well-controlled T2D neutrophils, thus restoring NET antibacterial capacity and promoting the wound healing process via fibroblast activation and differentiation. Conclusion: This study suggests that clarithromycin may add further advantage to well-controlled T2D patients, by enhancing their antibacterial defense and improving wound healing capacity of fibroblasts, through upregulation of LL-37 on NET structures.